Gambaran Pelaksanaan Trias Usaha Kesehatan Sekolah pada SD Inpres Boa di Kabupaten Rote Ndao - Tyrone Adithya Nabe; Limbu, Ribka; Tedju Hinga, Indriati A. (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
School Health Business needs to be run among other classes of school age community, school community comprising teachers, employees, students and parents of students being the most able to understand this. The need for coaching and guidance of children who are still in growth and development, health education through school is the most effective way compared to other efforts because schools are well organized and can spread modernization. This research aims to know the picture of the implementation of the TRIAS Business School Health At SD Inpres Bo’a District West Rote Regency Rote Ndao. The type of research used is observational descriptive research, the method used in this study is a survey method with data collection techniques using hacket. The data analysis in this study used descriptive analysis while the calculation used a percentage, sampling technique total sampling. The researchers took all samples with 32 of the teachers of 10, 2 employees and 20 students. The implementation of the UKS TRIAS Program at SD Inpres Bo’a has been running quite well with a percentage of 84.38% in the medium category. The principal and teacher are responsible and supportive in the coaching and development of TRIAS UKS in schools and engage in health education activities, health care and coaching of healthy school environments.